Uji Toksisitas Subkronis Dermal Emulgel Ekstrak Rimpang Jahe Merah terhadap Profil Hematologi dan Biokimia Tikus Wistar - Andrey Febrian (Fakultas Farmasi, 2026)
Red ginger (Zingiber officinale var. rubrum) has demonstrated effectiveness in treating painful diabetic neuropathy, but comprehensive safety evaluation through subchronic toxicity testing is required. This study employed a true experimental post-test only controlled group design using Wistar rats (aged 8–10 weeks) to evaluate the subchronic dermal toxicity and assess reversibility of potential toxic effects. Five groups (10 rats each; 5 males, 5 females) received emulgel extract at doses of 250, 500, and 1000 mg/kgBB applied dermally for 28 days, with a satellite group monitored for 14-day recovery period. Blood samples were analyzed for hematological parameters (hemoglobin, erythrocytes, leukocytes with differential, platelets) and biochemical markers (AST, ALT, BUN, creatinine; glucose, cholesterol, triglycerides). The results of this study indicates that red ginger extract emulgel induced significant dose-dependent alterations in leukocyte counts and differential composition, indicating HPA axis-mediated myelopoiesis activation. Female rats showed complete reversibility of hematological changes after recovery, while male rats exhibited persistent neutrophil, lymphocyte, and monocyte alterations. Biochemical parameters remained within normal physiological ranges despite statistically significant changes in creatinine at higher doses. These findings suggest that red ginger rhizome extract emulgel demonstrates a favorable safety profile with dose-dependent hematological effects, supporting its potential development as a therapeutic agent for painful diabetic neuropathy.
Reuploud Repository hasyim Juni 2026 Finalisasi Repo 23 Juni 2026_Yudi
Keywords: biochemical; hematology; red ginger emulgel; subchronic dermal toxicity; toxicity reversibility